Cradoscrupocellaria, a new bryozoan genus for Scrupocellaria bertholletii (Audouin) and related species (Cheilostomata, Candidae): taxonomy, biodiversity and distribution - Vieira, Leandro M.; Jones, Mary E. Spencer; Winston, Judith E. (Zootaxa, 2013)
A new genus, Cradoscrupocellaria n. gen., is erected for Scrupocellaria bertholletii (Audouin, 1826), reported as widespread in tropical and subtropical waters. Here we select a neotype of this species in order to establish its identity and distinguish it from morphologically similar species. We include redescriptions and figures of additional species now assigned to this new genus: Cradoscrupocellaria curacaoensis (Fransen, 1986) n. comb., Cradoscrupocellaria hirsuta (Jullien & Calvet, 1903) n. comb., and Cradoscrupocellaria macrorhyncha (Gautier, 1962) n. comb. Five additional species are assigned to the genus: Cradoscrupocellaria ellisi (Vieira & Spencer Jones, 2012) n. comb., Cradoscrupocellaria nanshaensis (Liu, 1991) n. comb., Cradoscrupocellaria reptans (Linnaeus, 1758) n. comb., Cradoscrupocellaria serrata (Waters, 1909) n. comb., and Cradoscrupocellaria tenuirostris (Osburn, 1950) n. comb. Eighteen new species are described: Cradoscrupocellaria aegyptiana n. sp., Cradoscrupocellaria arisaigensis n. sp., Cradoscrupocellaria atlantica n. sp., Cradoscrupocellaria calypso n. sp., Cradoscrupocellaria floridana n. sp., Cradoscrupocellaria galapagensis n. sp., Cradoscrupocellaria gautieri n. sp., Cradoscrupocellaria gorgonensis n. sp., Cradoscrupocellaria hastingsae n. sp., Cradoscrupocellaria insularis n. sp., Cradoscrupocellaria jamaicensis n. sp., Cradoscrupocellaria lagaaiji n. sp., Cradoscrupocellaria macrorhynchoides n. sp., Cradoscrupocellaria makua n. sp., Cradoscrupocellaria marcusorum n. sp., Cradoscrupocellaria normani n. sp., Cradoscrupocellaria odonoghuei n. sp., and Cradoscrupocellaria osburni n. sp.